LIGANDS FOR SELECTIVE REMOVAL OF LIPOPOLYSACCHARIDES FROM GRAM NEGATIVE BACTERIA - M. N. Kopitsyna (Журнал микробиологии, эпидемиологии и иммунобиологии, 2017)
Bacterial lipopolysaccharides (LPS) are highly toxic molecules released during the lysis of bacterial cells. They play important role in the pathogenesis of sepsis, and can contaminate pharmaceuticals, so removing them from aqueous solutions and biological fluids is an extremely important task. Structure of LPS and its toxicity for various animals are presented in this review. Various low- and high-molecular ligands, suitable for efficient binding and removal LPS from solutions are studied and demonstrated. The main attention is paid to the relationship between the chemical structure of the ligand and its ability to form strong complexes with LPS and the principles of creating selective ligands for the depyrogenation of pharmaceutical substances and the creation of hemoperfusion columns for the sepsis therapy.